Síntese de análogos de chalconas do tipo retinóide com potencial atividade biológica - (:unkn) unknown (Universidade Estadual de Goiás, 2008)
In the present work was related the study of the retinoid-like chalcones similar synthesis by the Claisen-Schmidt condensation between β-ionone and a benzaldeyde p-substitute derivative using NaOH or LiOH.H2O in solution (homogeneous catalysis) or the Mg and Al mixed oxide, OM-13 obtained from calcined hydrotalcite sample, MgAl-13 (heterogeneous catalysis) as catalysts in methanol or ethanol. The hydrotalcite and mixed oxide samples were submitted to physic-chemical characterization. The best results were obtained for (1E,4E)-1- phenyl-5-(2,6,6-trimethylcyclohex-1-enyl)penta-1,4-dien-3-one (3a) obtained by the reaction between -ionone and benzaldehyde catalyzed by NaOH at 333 K for 2 hours or LiOH.H2O at room temperature for one hour with medium yields of 38,0% and 57,9% respectively. The compost (1E,4E)-1-(4-nitrophenyl)-5-(2,6,6-trimethylcyclohex-1-enyl)penta-1,4-dien-3-one (3b) obtained between -ionone and p-nitrobenzaldehyde catalyzed by NaOH at room temperature for 1:30 hour yielded 53,0%, and (1E,4E)-1-(4-methoxyphenyl)-5-(2,6,6- trimethylcyclohex-1-enyl)penta-1,4-dien-3-one (3c) was synthesized between -ionone and pmethoxybenzaldehyde catalyzed by NaOH for 2 hours at 333 K. The use of mixed oxide, MO-13, as catalyst for the Claisen Schmidt reaction leaded a low conversions in the reaction conditions employed. The reaction products were analyzed by gaseous chromatography (GC). The products (3a) and (3b) were purified by recrystallization in methanol or ethanol and characterized by spectrometry‟s in the infrared (IR) and of nuclear magnetic resonance of 1H and 13C (NMR) and the product (3b) was analyzed by mass spectrometry. The IV, 1H and 13C NMR and mass spectrometric analysis allow concluding that was obtained the expected compounds.
Synthesis of “retinoid-like chalcones" similar with potential biological activity
Keywords: Catálise homogênea; Catálise heterogênea; Condensação de Claisen-Schmidt; Hidrotalcitas; Análogos de chalconas; Retinoides; Claisen-Schmidt condensation; Síntese Orgânica; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::QUIMICA ORGANICA; QUIMICA ORGANICA::SINTESE ORGANICA